A A - Banna, Triani; Gurning, Maylar; Sahetapy, Viona (An Idea Health Journal, 2022)
At the beginning of 2020, the world was shocked by the corona virus (Covid-19) outbreak which infected almost all countries in the world. The Word Health Organization (WHO) said that there were more than 215 countries that had confirmed Covid-19 on October 21, 2020, with 40,766,671 infected patients. Indonesia infected reached 368,842 people. West Papua Province infected with 3,688 people. Sorong Regency shows a total of 380 close contacts. The impact of mental health on Covid-19 on medical personnel as a whole, namely the presence of worry and feeling anxious about contracting the corona virus, worry of spreading it to family members, difficulty sleeping related to excessive anxiety, fear of contracting because of working in a risky unit and worrying because PPE is not up to standard in treatment for Covid-19. The purpose of this study was to describe the level of anxiety of nurses in health services during the Covid-19 pandemic at Dr. Jhon Piet Wanane, Sorong Regency. This type of research is a quantitative study using descriptive methods. The population was all nurses who served in RSUD Dr. Jhon Piet Wanane, Sorong Regency. A sample of 180 people. This research was conducted for 1 month. The results showed that out of 180 respondents, it was found that nurses experienced a severe level of anxiety, namely 71 (39.4), moderate anxiety, namely 59 (32.8%), mild anxiety, namely 37 (20.6%) and the least anxious, namely 13 (7.2%). The conclusion of this study is that most nurses experience moderate and severe anxiety. Suggestions for the nursing department of the hospital to form a stress management team to deal with the stress or anxiety experienced by nurses during the Covid-19 pandemic.